2009
DOI: 10.2118/117162-pa
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water-Based Drilling-In Fluids on Solids Invasion and Damage Characteristics

Abstract: Drilling the U-formation (shale and sandstone) in Saudi Arabia requires high drilling fluid density (±95 lbm/ft 3 ) to mechanically stabilize the shale and balance the reservoir pressure. Two fluids have been used to drill this formation: KCl/BaSO 4 /CaCO 3 and potassium formate/CaCO 3 drilling fluids. Barite is added in the first fluid with CaCO 3 to reduce the amount of solids needed to formulate the drillin fluid. However, BaSO 4 is insoluble in acids and requires chelating agents (DTPA) to remove it from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Al-Yami et al [63]. They observed that the filtrate from KCOOH RDF did not cause migration of kaolinite with booklet-form physiochemical characteristics, and the environmental scanning electron microscopy (ESEM) and energy-dispersive spectroscopy indicated precipitation of potassium chloride within the pore structures of the reservoir (Figure 8).…”
Section: Underground Reservoir-drilling Fluid Interaction-related Formation Damagementioning
confidence: 98%
See 1 more Smart Citation
“…Al-Yami et al [63]. They observed that the filtrate from KCOOH RDF did not cause migration of kaolinite with booklet-form physiochemical characteristics, and the environmental scanning electron microscopy (ESEM) and energy-dispersive spectroscopy indicated precipitation of potassium chloride within the pore structures of the reservoir (Figure 8).…”
Section: Underground Reservoir-drilling Fluid Interaction-related Formation Damagementioning
confidence: 98%
“…They observed that the filtrate from KCOOH RDF did not cause migration of kaolinite with booklet-form physiochemical characteristics, and the environmental scanning electron microscopy (ESEM) and energy-dispersive spectroscopy indicated precipitation of potassium chloride within the pore structures of the reservoir (Figure 8). Al-Yami et al [63] only considered one individual species-namely, booklet kaolinite-and did not consider other individual species of clay minerals of varying physicochemical characteristics, such as platy kaolinite, vermicular kaolinite, or blocky kaolinite. It is most often the case for kaolinite to become detached from grain walls and then migrate and flocculate or deflocculate after interaction, before being eroded by drilling fluids.…”
Section: Underground Reservoir-drilling Fluid Interaction-related Formation Damagementioning
confidence: 99%
“…There are six scenarios in which drilling fluids can cause a damage of the formation [213]: 1. fluid-to-fluid incompatibilities, e.g., emulsions generated between invading OBM filtrate and formation water; 2. rock-to-fluid incompatibilities, e.g., contact of potentially swelling smectite clay or deflocculatable kaolinite clay by nonequilibrium aqueous fluids, such as fresh water, that have the potential to reduce near-wellbore permeability severely; 3. solids invasion, e.g., the invasion of weighting agents or drilling cuttings into the formation; 4. phase trapping/blocking, e.g., the invasion and entrapment of waterbased fluids in the near-wellbore region of gas wells; 5. chemical adsorption/wettability alteration, e.g., changes in the wettability and fluid flow characteristics in the critical near-wellbore area because of emulsifier adsorption; 6. biological activity, e.g., the introduction of bacteria into the formation during drilling and the subsequent generation of slimes, which reduce the permeability. Moreover, in over-balanced drilling, solids invade the formation [214]. These invading particles, which are suspended in the drilling fluid, tend to plug the pore throats and cause a formation damage.…”
Section: Formation Damagementioning
confidence: 99%
“…Barite (BaSO 4 ) is a common weighting material used to attain the desired density of drilling and completion fluids [2,11] because barite has a high density, low production cost, and less environmental impact [12,13]. However, the invasion of solid particles causes formation damage and reduces the permeability near the wellbore [14,15]. Another issue encountered with barite-weighted fluids is solids sag or barite sag.…”
Section: Introductionmentioning
confidence: 99%